Effectiveness of locally produced ready to use supplementary food on hemoglobin, anthropometrics, and plasma micronutrients concentrations of 6 to 23 months age children: a non-randomized community-based trial from Pakistan - Khan, Aslam; Ul-Haq, Zia; Fazid, Sheraz; Fatima, Sadia; Muhammad, Nawshad; Ahmed, Jawad; Manoharadas, Salim; Safi, Sher Zaman; Habib, Ijaz; Garzon, Cecilia; Ihtesham, Yasir; Zahid, Fareeda; et al. (Frontiers in Nutrition, 2023)
Background Micronutrient deficiencies including vitamin A, vitamin D, and zinc are highly prevalent in children below 5 years of age in low and –middle-income countries. We aimed to evaluate the effectiveness of ready-to-use Lipid-based Nutrient Supplement—Medium Quantity (LNS-MQ) local name “Wawa-mum” on plasma micronutrient status, hemoglobin concentration and anthropometric measurements. Methods A community-based non-randomized trial was conducted in the Kurram district of Khyber Pakhtunkhwa from January 2018 to June 2019. A total of 110 children aged 6 to 23 months old were recruited and allocated to the intervention and control arm of the study. A total of 57 children in the intervention arm received a daily ration of 50 g of Wawa-mum, for one year. To assess the impact of the intervention on primary outcome measures, i.e., serum vitamin A, D concentration, plasma zinc, and hemoglobin concentration. Blood samples were collected at baseline and after one year following the intervention. The vitamins concentration in serum were assessed using Enzyme-Linked Immunosorbent Assay (ELISA) and plasma zinc by atomic absorption spectrometry. The hemoglobin concentration was measured by an automated hematology analyzer. A 24-h dietary recall interview was used to assess the nutrient intake adequacy. Multivariate Linear regression models were used to analyze the outcomes while controlling for potential confounders. Results In the intervention arm, children had on average 6.2 μg/dL (95% CI 3.0–9.3, value of p<0.001) increase in the serum vitamin A concentration, 8.1 ng/mL (95% CI 1.3–14.9, value of p 0.02) increase in serum vitamin D concentration and 49.0 μg/dL (95% CI 33.5–64.5, value of p<0.001) increase in the plasma zinc concentration, and 2.7 g/dL (95% CI 2.0–3.3, value of p<0.001) increase in hemoglobin concentration while adjusted for covariates. An addition, length-for-age z-score (LAZ), weight-for-length z-score (WLZ), weight-for-age z-score (WAZ), and prevalence of undernutrition including stunting, wasting, and underweight were calculated as a secondary outcome to investigate the impact of micronutrients on growth parameters, that has been improved significantly after receiving the Wawa-mum. Conclusion Wawa-mum (LNS-MQ) is an effective intervention to improve the micronutrient status, hemoglobin concentration, and growth parameters in 6 to 23 months children, which can be scaled up in the existing health system to address the alarming rates of under nutrition in Pakistan and other developing countries. Clinical trial registration https://doi.org/10.1186/ISRCTN94319790, ISRCTN94319790.